2002
DOI: 10.1029/2002ja009293
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional multispecies MHD studies of the solar wind interaction with Mars in the presence of crustal fields

Abstract: [1] We present the results of model calculations using a multispecies MHD model of the interaction of the solar wind with Mars. The three ions considered are H + , O 2 + , and O + , representing the solar wind and the two major ionospheric ion species, respectively. The calculations indicate that the presence of a hot oxygen corona does not, within the resolution and accuracy of the model, lead to any significant effect on the dayside bow shock and ionopause positions. Next the trans-terminator fluxes and esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
165
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 33 publications
5
165
0
Order By: Relevance
“…Ma et al (2002) also described the general circulation of ionospheric plasma which, in agreement simulations of Venus' plasma interaction, was upward on the day side ionosphere, day to night at higher altitudes, downward on the night side below about 250 km altitude, and down Mars magnetotail at higher altitudes. Ma et al (2004) improved on the model published in Ma et al (2002) by including a new spherical grid structure, better resolution near the inner boundary, and an additional species (CO + 2 ). This model was used to quantify ion outflow from Mars for several orientations of crustal magnetic field and for different solar wind conditions.…”
Section: Mhd Models Of Mars' Interaction With the Solar Windmentioning
confidence: 71%
See 4 more Smart Citations
“…Ma et al (2002) also described the general circulation of ionospheric plasma which, in agreement simulations of Venus' plasma interaction, was upward on the day side ionosphere, day to night at higher altitudes, downward on the night side below about 250 km altitude, and down Mars magnetotail at higher altitudes. Ma et al (2004) improved on the model published in Ma et al (2002) by including a new spherical grid structure, better resolution near the inner boundary, and an additional species (CO + 2 ). This model was used to quantify ion outflow from Mars for several orientations of crustal magnetic field and for different solar wind conditions.…”
Section: Mhd Models Of Mars' Interaction With the Solar Windmentioning
confidence: 71%
“…The strongest of the magnetic fields (which occur mostly in the southern hemisphere) were placed in the sub-ram direction. Ma et al (2002) found that crustal magnetic fields did not effect the location of the bow shock but did effect the location of the MPB. The interaction between the piled-up IMF field in the MPB and the crustal magnetic fields also produced small-scale magnetic structures known as magnetocylinders, which had been observed by spacecraft (Mitchell et al 2001).…”
Section: Mhd Models Of Mars' Interaction With the Solar Windmentioning
confidence: 95%
See 3 more Smart Citations